Attendant psycho-social hearing reactions of the elderly with presbycusis in rural and urban areas of South-West Nigeria (2013)
This study investigated the psycho-social hearing reactions of the elderly with experience of age-related hearing loss in Lagos, Oyo, and Ogun states of Nigeria. Descriptive survey research design was adopted for the study. Two hundred and forty participants were selected through Multi-stage sampling technique from both the rural and urban areas of the three states sampled. Age-related Hearing loss Reaction Scale (A-RHLS, r= 0.85) was used as instrument for data collection. Three null hypotheses were tested at 0.05 level of significance, and data were analysed using Chi-square. The findings revealed that 178 (74.2%) of the participants exhibited negative psycho-social hearing reactions as against 92 (25.8%) who manifested positive psycho-social hearing reactions. The females from the rural areas showed positive psycho-social hearing reactions, compared to their counterparts from urban areas. The study thus confirms a trend of psychosocial hearing reactions among the elderly in Nigeria. The study recommends that elderly individuals with hearing loss be audiologically evaluated and rehabilitated holistically, as this will help them to develop an enduring socioemotional coping strategies even as their hearing ability degenerates with increase in age.